Diagnosis of Gardnerella Vaginalis Isolated from Vaginal Discharge of Women in Babylon Province - Sawsan Talal. Abdullah, Azhar O. Althahab, Sura I.A. Jabuk, (Pakistan Journal of Medical & Health Sciences, 2022)
Bacterial vaginitis is a prevalent condition that affects women all over the world and is the most common cause of vaginitis that has been recognized. Gardnerella vaginalis was found to be the most often identified pathogen in the vaginal discharge samples taken from patients diagnosed with vaginal infections. Two hundred (100 for Amsel test, 100 for culture) vaginal samples were taken from 100 women (two swaps from each woman) by the gynecologist to study the identification of G. vaginalis by Wet smear, Direct staining, Amsel test, Culture identification, and Molecular identification by 16sRNA. The result of Amsel test presents 10(18%) samples positive to four Amsels criteria and other samples positive to three of Amsel’s criteria from the 56 samples for positive Gardnerella vaginalis samples. The result of culture, biochemical, and Gram stain present the percentage of samples positive for G. vaginalis was 56 (56%). Electrophoresis of the PCR results of G. vaginalis DNA extracted from vaginal samples revealed the presence of a band with a size of 300 base pairs in only 12 of the 56 positive culture samples. As a result, it is imperative that diagnostic techniques for the detection of this illness be improved, particularly in terms of differentiating BV from other potential causes of vaginal infections